Неповага до ашикської літератури - Саім Сакаоглу (Народна творчість та етнографія, 2010)
Ashik literature is one of the important branches of Turkish literature. Its true worth however cannot be seen by many people. Ashik poems have been easily changed. Moreover, a poem of an ashik, for example, has been attributed to another ashik. This is resulted from ignorance or some deliberate attempts. Thus, researchers have to be well-informed about the field of ashik literature. Âşık edebiyatı, edebiyatımızın önemli dallarından biridir. Ancak bu edebiyatın değeri yeterince bilinememiştir. Âşık şiirleri kolaylıkla değiştirilmiştir. Hatta bir şiir başka bir âşığın adına bağlanmıştır. Bunda bilgisizliğin ve kasıtlı olmanın rolü vardır. Araştırıcılar bu alanı çok iyi öğrenmek zorundadır.